Defective ribosomal protein gene expression alters transcription, translation, apoptosis, and oncogenic pathways in Diamond-Blackfan anemia - Gazda, H. T.; Kho, A. T.; Sanoudou, D.; Zaucha, J. M.; Kohane, I. S.; Sieff, C. A.; Beggs, A. H. (Stem CellsStem CellsStem Cells, 2006)
Diamond-Blackfan anemia (DBA) is a broad developmental disease characterized by anemia, bone marrow (BM) erythroblastopenia, and an increased incidence of malignancy. Mutations in ribosomal protein gene S19 (RPS19) are found in approximately 25% of DBA patients; however, the role of RPS19 in the pathogenesis of DBA remains unknown. Using global gene expression analysis, we compared highly purified multipotential, erythroid, and myeloid BM progenitors from RPS19 mutated and control individuals. We found several ribosomal protein genes downregulated in all DBA progenitors. Apoptosis genes, such as TNFRSF10B and FAS, transcriptional control genes, including the erythropoietic transcription factor MYB (encoding c-myb), and translational genes were greatly dysregulated, mostly in diseased erythroid cells. Cancer-related genes, including RAS family oncogenes and tumor suppressor genes, were significantly dysregulated in all diseased progenitors. In addition, our results provide evidence that RPS19 mutations lead to codownregulation of multiple ribosomal protein genes, as well as downregulation of genes involved in translation in DBA cells. In conclusion, the altered expression of cancer-related genes suggests a molecular basis for malignancy in DBA. Downregulation of c-myb expression, which causes complete failure of fetal liver erythropoiesis in knockout mice, suggests a link between RPS19 mutations and reduced erythropoiesis in DBA.
Gazda, Hanna TKho, Alvin TSanoudou, DespinaZaucha, Jan MKohane, Isaac SSieff, Colin ABeggs, Alan HengR01 HL064775/HL/NHLBI NIH HHS/R01-AR044345/AR/NIAMS NIH HHS/P01-HL99021/HL/NHLBI NIH HHS/NS40828/NS/NINDS NIH HHS/P01 NS040828/NS/NINDS NIH HHS/R01 AR044345/AR/NIAMS NIH HHS/P50 NS040828/NS/NINDS NIH HHS/R01 NS047527/NS/NINDS NIH HHS/P01-NS40828/NS/NINDS NIH HHS/R01-NS047527/NS/NINDS NIH HHS/R01-HL64775/HL/NHLBI NIH HHS/Research Support, N.I.H., ExtramuralResearch Support, Non-U.S. Gov'tDayton, Ohio2006/06/03 09:00Stem Cells. 2006 Sep;24(9):2034-44. doi: 10.1634/stemcells.2005-0554. Epub 2006 Jun 1.
Keywords: *Gene Expression Regulation; *Transcription, Genetic; Adult; Anemia, Diamond-Blackfan/*genetics; Animals; Apoptosis/*genetics; Case-Control Studies; Cell Separation; Erythroid Precursor Cells/cytology/metabolism/pathology; Female; Genome, Human/genetics; Humans; Male; Mice; Microarray Analysis; Mutation/genetics; Neoplasms/*genetics; Protein Biosynthesis/*genetics; Proto-Oncogene Proteins c-myb/genetics; Reproducibility of Results; Ribosomal Proteins/*genetics; RNA, Ribosomal, 18S/genetics